An Operando Study of the Initial Discharge of Bi and Bi/Cu Modified MnO2. Issue 13 (15th September 2018) - Gallaway, Joshua W.; Yadav, Gautam G.; Turney, Damon E.; Nyce, Michael; Huang, Jinchao; Chen-Wiegart, Yu-chen Karen; Williams, Garth; Thieme, Juergen; Okasinski, John S.; Wei, Xia; Banerjee, Sanjoy
Abstract : It was recently reported that inclusion of Cu in Bi-modified MnO2 cathodes allowed over 1000 cycles at nearly the full capacity of 617 mAh/g-MnO2, at a high areal capacity of 28 mAh/cm 2 . To better understand the molecular mechanism by which Bi and Cu impart rechargeability, cathodes prepared by physical mixing of MnO2 and Bi2 O3 were studied during initial discharge at an areal capacity of 57.4 mAh/cm 2, both with Cu (MDBC) and without (MDB). These were compared to the base case with MnO2 only (MD). It is demonstrated that there are two distinct regimes of Mn II production during the second electron regime of discharge. In standard MD cathodes, the first regime results in an amorphous product formed simultaneously with Mn3 O4, while the second results in crystalline Mn(OH)2 . When MnO2 is Bi-modified, crystalline Mn(OH)2 is formed in both regimes and Mn3 O4 is absent. Bi and Cu are observed to have a structural effect on the α-MnOOH discharge intermediate. Cu II is shown to be electrochemically active at the surfaces of MnO2 particles, reducing to Cu I and Cu 0 . Reversible potentials suggest Mn II would act as a redox mediator, reducing Cu II . Fluorescence mapping provides evidence for occurrence of this phenomenon.